New Virus Genome Sequences of the Guama Serogroup (Genus Orthobunyavirus, Family Bunyaviridae), Isolated in the Brazilian Amazon Region - Carvalho, Valéria L. (Genome Announc, 2017)
This is the first announcement of two nearly complete viral genome sequences belonging to the Guama serogroup (genus Orthobunyavirus, family Bunyaviridae) isolated in the Brazilian Amazon region: Mirim virus (MIRV; BEAN7722) and Ananindeua virus (ANUV; BEAN109303).